Light scattering in LiCoPO4 single crystal: analysis of the vibrational spectrum - Fomin, V. I.; Gnezdilov, V. P.; Kurnosov, V. S.; Peschanskii, A. V.; Eremenko, V. V.; Rivera, J.-P.; Gentil, S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
In a single crystal of LiCoPO4 Raman scattering has been studied in a wide temperature range. Thirty-two of the 36 Raman-active vibrational modes predicted by group-theory analysis were detected. The experimental lines are identified on the basis of their polarization rules, frequency position, and temperature behavior.